The mediator role of body image-related cognitive fusion in the relationship between disease severity perception, acceptance and psoriasis disability - Almeida, Vera (2020)
Psoriasis is a long-term skin disorder without a cure, whose patients are particularly susceptible to mental health diseases. Using a sample of patients diagnosed with psoriasis, this study aimed to: (1) identify the clinical and positive psychological variables that contribute the most to psoriasis disability and (2) assess the mediator role of body image-related cognitive fusion in the relation between disease severity perception and acceptance and self-compassion, on one hand, and psoriasis disability on the other. This is an initial cross-sectional exploratory study, with 75 patients diagnosed with psoriasis (males 52%; mean age 54.99 ± 13.72) answering a sociodemographic and a clinical questionnaire, the Psoriasis Disability Index (PDI), the Cognitive Fusion Questionnaire—Body Image (CFQ-BI), the Acceptance and Action Questionnaire—II (AAQ-II), and the Self-Compassion Scale (SCS). Descriptive and inferential statistics were used to characterize and assess the measures and the final model used. Through path analysis and a hierarchical multiple linear regression, it was found that the variables that significantly contributed to psoriasis disability were years of education, impact on social life and body image, explaining 70% of the variance. Body image-related cognitive fusion was a significant mediator in the relationship between disease severity and acceptance, and psoriasis disability. The implications of this study are considered to be extremely relevant, since it will allow additional information to be provided to psoriasis patients, appropriated to their educational level, aiming to reduce distorted perceptions of disease severity and intervene in the ability to accept this specific and important chronic health condition.